Pengaruh Financial Technology dan Inklusi Keuangan Terhadap Perilaku Keuangan Mahasiswa Universitas Negeri Padang Jurusan Pendidikan Ekonomi - Radia Fatma; Sumiati Sumiati (Journal of Innovative and Creativity (Joecy), 2026)
Financial behavior is an individual's ability to manage and make financial decisions in daily life. This study aims to analyze the effect of financial technology and financial inclusion on students' financial behavior. This research uses a quantitative method with a sample of 80 respondents selected using simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that financial technology has a positive and significant effect on financial behavior, while financial inclusion has a negative and significant effect on financial behavior. This indicates that although access to financial services is increasing, it does not always improve financial management behavior among students.